Efecto de la densidad de plantación sobre la resistencia al corte y compresión paralela a las fibras en madera de Eucalyptus grandis Hill (ex Maiden) de 11 años de edad - Bragañolo, Adelaida; Barth, Sara Regina; Keller, Aldo Esteban; Feldmann, Alexis; Primo, Agustín; Morel, Matías; Winck, Rosa Ángela; Aquino, Diego Rolando; Knebel, Otto Eduardo (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2023)
Certain uses of wood make the mechanical properties of wood relevant. Therefore, it is important for the forester to know the characteristics of the wood to be obtained according to the adopted silvicultural management. The influence of initial planting density on shear strength and compression axial or parallel to the fibers was studied in 11-years-old Eucalyptus grandis wood. The evaluated treatments did not significantly influence the studied mechanical properties, presenting differences between the first and second sawn log in the case of compression.